1988
DOI: 10.1366/0003702884429869
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiplicative Scatter Correction (MSC) and Linearity Improvement in NIR Spectroscopy

Abstract: Near-infrared (NIR) reflectance spectra of five different food products were measured. The spectra were transformed by multiplicative scatter correction (MSC). Principal component regression (PCR) was performed, on both scatter-corrected and uncorrected spectra. Calibration and prediction were performed for four food constituents: protein, fat, water, and carbohydrates. All regressions gave lower prediction errors (7–68% improvement) by the use of MSC spectra than by the use of uncorrected absorbance spectra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(236 citation statements)
references
References 10 publications
7
218
0
Order By: Relevance
“…The inverse MSC method was the best scatter correction of the FSC samples, whereas the standard MSC method was the best scatter correction of the XDS samples (Isaksson and Naes, 1988). The best mathematical pre-processing were 0,0,1,1 and 2,4,4,1 treatments for FSC and XDS samples, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The inverse MSC method was the best scatter correction of the FSC samples, whereas the standard MSC method was the best scatter correction of the XDS samples (Isaksson and Naes, 1988). The best mathematical pre-processing were 0,0,1,1 and 2,4,4,1 treatments for FSC and XDS samples, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Previous work (Geladi et al, 1985;Isaksson & Naes, 1988) has demonstrated that MSC of spectral data results in better linear ®t between NIR data and chemical concentratons, better spectral interpretability and improved prediction results compared with uncorrected data. The multivariate calibration method PLS (partial least squares) regression was used.…”
Section: Discussionmentioning
confidence: 99%
“…The MSC method uses linear regression of the spectral variables vs. the average spectrum and simultaneously corrects for both multiplicative and additive scatter effects (Isaksson and Naes, 1988). This method has attractive conceptual properties and has given many promising results in other studies (Helland et al, 1995, Geladi et al, 1985, Maleki et al, 2007.…”
Section: Spectral Analysismentioning
confidence: 99%